School Inclusion Policy and Curricular Practices: Teaching Strategies for Target Audience Conceptual Elaboration of Special Education - Hostins, Regina Célia Linhares; Jordão, Suelen Garay Figueiredo (Education Policy Analysis Archives, 2015)
In Brazil, the inclusive education policy and curriculum practices of disabilities students have been the subject of inquiry and debate. These students, despite having guaranteed access to regular education, find restrictions in their schooling processes due to lack of their learning characteristics. In regular school and in special education still predominate questions about what and how to teach these students and which curriculum and practices could improve their conceptual elaboration processes. In this paper, we analyze testimonies of teachers, (resulting from group interview) and episodes of interactions and teaching actions effected in specialized education support (Salas de Recurso Multifuncional -SRM) from the regular schools in the Vale do Itajaí, SC. The purpose is to problematize: orientations of policy, curricular practices and the role of SRM in these students’ schooling. The testimonies and analyzed episodes are an illustrative excerpt of collaborative research with SRM’ teachers in 2012/2013, which is linked to two National Observatories of Special Education, articulated to the CAPES’ National Education Observatory Program and to the Foundation for Research and Innovation of the State of Santa Catarina (FAPESC). The results of the research indicate contradictions, segmentations and the fragility of policy in relation to the locus and the processes of schooling and the potential curricular practices of the disabilities students’ conceptual elaboration.